Research and the New Communication Technologies: Forecast and Possibilities - Clifford W. Scherer (Journal of Applied Communications, 1986)
If you read the publications of the new communication technologists, the trade publications especially, you can quickly become enamored with the incredible potential many of the advances in communication technology offer. (See for example such publications as PC Magazine, Mini-Micro Systems, and MISWeek).